Study of Industrial Pollution and Its Effect on Nile Tilapia in Marryotia Canal - Jasim, Amany M.; Shehab, Gehan G.; Soliman, Khadra; El- Hakim, Taheia Abd (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study was carried out to assay the bioaccumulation of ammonia ,nitrite ,nitrate in fresh water and the concentration of heavy metals (Lead, Cupper, Cadmium, Manganes and Zinc) in water and tissues of Tilapia niloticus selected from El-marryotia canal (one of the river Nile ramification in Al-Giza city) in Egypt, samples were collected during the period of July to October 2011 to determine water safety for human consumption and the hazardous effect of these metals on the histopathology of selected tissues and organs of fish. Two samples were collected from two locations of canal, pH of water samples were measured and the concentration of ammonia, nitrate and nitrite were determined in these samples. Twenty Tilapia were also collected from different locations of the canal, One gram of liver, abdominal and dorsal muscles tissue from each fish were taken for determination of lead, Cupper, Cadmium, manganese and Zinc in the selected tissues. Specimens of gills, muscles, liver, kidney and intestine from each fish were fixed in 10% buffered neutral formalin, and processed for pathological study. The results revealed that water samples polluted with ammonia, nitrite and nitrate respectively.,significant differences were recorded in concentration of Mn and Zn in both water samples. The mean concentration of Pb was 0.216±0.0108, 0.204±0.009 and Mn 0.901±0.041, 0.73±0.003 in both water samples which was above the World Health Organization safety standard, the results indicated that water were polluted with both two heavy metals. More concentration of Pb1.362±0.0657 was noted in liver of fish , concentration of Pb (1.2±0.062), Cd (0.01.2±0.062) was the highest in abdominal muscles and lowest in the remaining tissues of fish , the mean concentration of Cu (0.6.2±0.032) was higher in abdominal muscle , Mn (0.54±0.02) and Zn (1,19.2±0.054) was more concentrated in dorsal muscles and all the heavy metals studied gave results with the permissible limits in fish tissue recorded by the standards of WHO. The main histopathological changes observed were edema and sloughing of lamellar epithelia in gills of fish. In liver, it was noticed vacuolation of most hepatocytes with nuclear pyknosis . The findings in kidneys exhibited the presence of periglomerular edema and vacuolar degeneration of most of renal tubules .The fish muscle showed degeneration and edema with focal areas of necrosis of some muscle fibres.